RESEARCH OF THE INFLUENCE OF THE QUALITY OF THE WORKING FLUID ON THE EFFICIENCY OF THE HYDRAULIC SYSTEM - Salimova Shaxrizoda Sanjar kizi (Web of Journals Publishing, 2024)
Recently, the main problem in the operation of hydraulic fluids of hydraulic mining machines is contamination with various small rock, dust impurities. As a result, parts of such machines quickly wear out. The article deals with the purification of contaminated liquids by clarifying the content of contaminated mixtures. In particular, some physical properties were studied (solubility, density, viscosity in organic solvents). The viscosity of the samples examined after distillation decreased compared to the initial samples.
Keywords: Hydraulic system, working fluids, viscosity, density, pollution components, working fluid purity class.